Are riparian vegetation flow response guilds transferable between rivers?. (22nd December 2022) - Cubley, Erin S.; Cooper, David J.; Merritt, David M.
Abstract: Understanding the current distribution of riparian plant species is essential for predicting their expansions or contractions in response to flow alterations due to climate changes or direct human actions. Riparian vegetation flow response guilds are assemblages of species that have common functional traits and are hypothesised to respond similarly to fluvial disturbance and water availability along rivers. Species distribution models using guilds may be useful within and across catchments, regions, and continents where floristic composition differs. We examined the distribution of riparian vegetation guilds along gradients of depth to groundwater and inundation exceedance probability (EP) on three rivers in the Colorado River basin and modelled the response of each guild to simulated changes in river flows and alluvial groundwater depth. Groundwater guild distribution models were transferable for the tall tree and flood‐tolerant shrub guilds, but groundwater depth and EP thresholds differed between reaches. Optimal groundwater levels for tall trees and flood‐tolerant shrubs were shallower in Colorado due to higher floodplain groundwater levels and more gentle sub‐surface groundwater gradients. Riparian vegetation guilds were better predicted by groundwater depth than EP while generalist upland guilds were excluded from areas frequently inundated. Presence of the tall tree guild (e.g., Populus fremontii ) was predicted by depth to groundwater at all free‐flowing reaches but was not predicted at the one reach where flows are regulated by an upstream dam. In higher elevation reaches, models predicted riparian vegetation guild occurrences with less accuracy, suggesting the influence of other factors such as competition or water contributions from surrounding hillslopes. Scenarios that imposed a groundwater decline indicated that extinctions of both tall trees and flood‐tolerant shrubs (e.g., Salix exigua ) could occur in some reaches, depending on future groundwater contributions from hillslopes and the river. Our study demonstrates that river reaches with different plant species composition can have similar guild compositions and the occurrences of these guilds are predicted by hydrologic conditions. Depth to groundwater had a stronger magnitude effect on guild occurrence, highlighting the importance of this less frequently quantified variable in river studies. Our results suggest that the relationship between riparian flow response guild occurrence and hydrologic conditions are transferable between river reaches with differing flow regime, elevation, and climate for some, but not all guilds. Although guilds may respond in similar ways to groundwater depth and flooding, they are not all well predicted by hydrologic condition alone. Guild distributions may be transferable between river systems, but prediction accuracy increases when models are grouped based on reach‐scale hillslope groundwater contributions, elevation, and valley setting.